THE CONCEPT OF MANAGERIAL ACTIVITY AND ITS FUNDAMENTAL COMPONENTS - Berdimuratov Adkham Khayrulla uglu; Shamsiyeva Nigina Baxriddin qizi (Modern American Journals, 2025)
This article analyzes the key components of the managerial activity of directors of preschool educational institutions and their role in the management process. Based on the views of scholars in the field, the study highlights the importance of the core functions of managerial activity — planning, organizing, leading, and controlling — and explains their significance in ensuring effective management within preschool institutions. Furthermore, the practical relevance and interrelationship of these components are examined from a scientific and methodological perspective.
Keywords: Managerial activity, preschool education, management, planning, organizing, leading, controlling, managerial components, director of an educational institution, management process.